Distopia censurada pela ditadura civil-militar brasileira: a sociedade representada na obra cinematográfica Laranja mecânica (1971) - Silva, José Emanoel Martins da (2021)
A Clockwork Orange, the film, released in 1972, directed and scripted by Stanley Kubrick, is an adaptation of the literary work by Anthony Burguess, with the same name, but written in 1961. The cinematographic work addresses a dystopian society that alerts, on stage, for various problems of a society in possible decay. Here, a group of young people like to go out at night to carry out thefts, among other crimes. The leader of this group is called Alex, who is the main character in the plot. At one point, Alex is arrested, being sentenced to fourteen years in prison for murdering a woman; in the prison, the boy wants to be free soon and agrees to undergo a still experimental treatment. After participating in the treatment, called “Ludovico Method”, and having his sentence reduced, he is released from his prison; however, the side effects of the treatment show to go beyond what Alex expected. With an emphasis on cinematographic narrative and the historical context of the 1960s, also covering, briefly, previous and subsequent decades, this study seeks to understand the relationships between History, Cinema, fiction and the possible relationships of cinematographic work A Clockwork Orange with the context of Europe and the United States, as well as the Brazilian Civil-Military Dictatorship of 1964. This research, therefore, also aims to understand how the representations related to the society that produced the work are presented in the film, as well as understand the possible connections with the post-coup period of 1964 in Brazil, through documents found online, the way in which Alex presents himself as an aesthetic character. The research also addresses actions of a military operation during the Brazilian Civil-Military Dictatorship, with Manoel Conceição Santos, entitled “Operação Búfalo”. For the methodological approach of the film, together with the methods of film analysis proposed by Francis Vanoye and Anne Goliot-Lété, Laurent Jullier and Michel Marie, it is possible to see that the analyzed film goes beyond a fictional narrative, relating to different areas with the conjuncture of its production period, presenting the expectations of the Western Society for the period of production of the work. In order to carry out the historiographic approach, as mentioned by John W. Creswell, in his book Qualitative investigation and research project (2014), the work is developed in a qualitative research method, starting from case research. Thus, several authors, from different areas of study of the Human Sciences, are incorporated throughout the text. The author is linked to the Culture, Migrations, and Labor research line in the Postgraduate Program in History at the Federal University of Santa Maria.